Characteristics and frequency of tuberculosis before and during the COVID-19 pandemic among adults treated in a primary healthcare center in Lima, Peru, 2019–2020 - Calixto E., Franco (2023)
Objective: To determine the characteristics and frequency of patients aged over 18 years with tuberculosis (TB) before (2019) and during (2020) the COVID-19 pandemic in a healthcare center (CS) in Lima, Peru. Materials and methods: A descriptive retrospective study that included medical records of 100 patients aged > 18 years enrolled in the TB program at CS Los Libertadores (SMP-Lima, Peru) from 2019 to 2020. Sociodemographic (sex, origin, age), clinical (admission/discharge status, body mass index, comorbidities, TB infection site, type of resistance, treatment regimen) and laboratory (smear microscopy, culture, drug susceptibility testing) variables were analyzed. Patients who did not have all the variables were excluded. An Excel database was prepared and a descriptive statistical analysis of the qualitative variables, expressed in frequencies, and quantitative variables, expressed in measures of central tendency (mean) and standard deviation, was performed using IBM SPSS Statistics. TB prevalence per year was determined, according to the population assigned to the healthcare center. Said information was obtained through the Tuberculosis Management Information System (SIGTB). Results: TB prevalence was 0.0015 % (49 patients) in 2019 and 0.075 % (51 patients) in 2020. In both years, the male sex and the age group between 18 and 29 years prevailed, and the most common site of infection were the lungs. In 2020, an increase in HIV comorbidity and mortality rate (0.074) was observed, as well as more positive smear microscopy cases. Conclusions: TB prevalence was higher in 2020, the first year of the COVID-19 pandemic, due to a reduced approach to TB programs as a result of the situation imposed by the pandemic. In addition, TB mortality rates raised in the same year, probably due to an increase in treatment dropouts or HIV and diabetes comorbidity rates.